2005
DOI: 10.1111/j.1399-6576.2005.00862.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral microdialysis and Ptio2 for neuro‐monitoring before decompressive craniectomy

Abstract: We report the case of a young patient with post-traumatic, intractable, intracranial hypertension leading to craniectomy. This intracranial hypertension was preceded by focal signs of ischemia diagnosed through P(ti)O2 monitoring and cerebral microdialysis, and occurred a few hours prior to a decrease in cerebral perfusion pressure below 60 mmHg. The neurological outcome was satisfactory with a Glasgow Outcome Scale of 4 at 3 months. We discuss the potential interest of such neuro-monitoring to determine the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 16 publications
1
14
0
1
Order By: Relevance
“…And finally, does elevation of ICP matter if clinically adequate levels of CPP are maintained? Reports from several authors suggest that metabolic derangements detectable with microdialysis can indeed precede substantial rises in ICP (Belli et al, 2008;Boret et al, 2006). This relationship was also seen in some of our patients, however, far more common observations included (near) simultaneous changes in ICP and LP ratio or other metabolic parameters, or episodes where ICP elevations were not associated with any change in biochemistry, before or after an event.…”
Section: Icp and Microdialysissupporting
confidence: 73%
“…And finally, does elevation of ICP matter if clinically adequate levels of CPP are maintained? Reports from several authors suggest that metabolic derangements detectable with microdialysis can indeed precede substantial rises in ICP (Belli et al, 2008;Boret et al, 2006). This relationship was also seen in some of our patients, however, far more common observations included (near) simultaneous changes in ICP and LP ratio or other metabolic parameters, or episodes where ICP elevations were not associated with any change in biochemistry, before or after an event.…”
Section: Icp and Microdialysissupporting
confidence: 73%
“…Another study has concluded that " …pbtO2 monitoring could be an important tool for timing craniectomy in the future" [221]. This report is supported by a case report [205]. The effects of DCH, which represents a very invasive treatment option and which is considered an ultimate surgical treatment option has also been studied: "DCH in the treatment of severe brain injury is associated with a significant improvement in brain oxygenation" [6].…”
Section: Decompressive Craniectomy and Ventricular Drainagementioning
confidence: 73%
“…There are publications also from Australia [38,[198][199][200], Austria [53,85], Brazil [58], Canada [93,118,132,135,139], China [9, 201,202], Croatia [203], the Czech Republic [204], Denmark [134]; Finland [134], France [43,77,114,205,206], Greece [207], Hungary [141], India [208], Japan [140,146,167,209], Portugal [64]; Russia [210,211], Singapore [2,4,10,16,74,212,213]; Serbia [214]; South Africa [26,28,35], South Korea [127], Sweden [90,134,215], Switzerland [11,216,217]...…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…8 However to offer added value over and above that provided by other intracranial monitors, cerebral MD must not only guide treatment, but do so in a way that reduces the burden of secondary brain injury and thereby offer the potential to improve functional outcome in survivors.…”
Section: Clinical Applications Of MD Monitoringmentioning
confidence: 99%